What is worth knowing about the establishment from a work safety point of view - Bujnóczki, Tibor; Zákányi Mészáros, Renáta (International Journal of Engineering and Management Sciences, 2019)
Under establishment, we mean the process that results in the creation of a new unit (eg factory, plant, office, etc.), a workplace or an existing one what will be renewed, expanded or restructured, or installed; installed on a machine, plant, appliance, whether or not for productive or non-productive purposes. It is generally true that the design, construction, use and subsequent operation of workplaces, facilities, technology, materials, energy, personal protective equipment; production, distribution, import, transportation, movement, use and use of workplaces; in the absence of these, the requirements of the scientific-technical standard can be expected. An employer, operator, and service provider must adapt to market conditions. Accordingly, it should monitor the expectations of customers, business partners, market changes, trends to adapt to expectations, and therefore constantly develop their products, services, produce reliable quality, ensure that quality meets the market expectations providing personal and material conditions to ensure that employees can effectively and safely meet market expectations. The recognized business perception of the employer is to accomplish the above, the objectives to be achieved must be formulated, priority should be given to the potential risks (with particular regard to occupational safety risks) to be measured, measures to be taken to ensure effectiveness, short-, medium- and long-term planning, investment.